Solution Focused Brief Counseling untuk Meningkatkan Motivasi Belajar Siswa - khairul bariyyah (JURNAL KONSELING GUSJIGANG, 2019)
There are still many students who have low learning motivation so that it hinders the learning process. The purpose of this study was to determine the effectiveness of Solution Focused Brief Counseling in increasing student motivation in junior high school. The research method used in this study was an experimental method with the design of one group pretest-posttest design. The subjects in this study amounted to 5 students who were determined based on the Purposive Sampling technique with a low category pretest scale score. The results showed that there were differences between the values of the pretest and posttest. The level of learning motivation of the research subjects from the pretest average score of 58.4 which is included in the low category, increased to an average of 91.2 when the posttest was included in the medium category. Based on the Wilcoxon test obtained a significance value of 0.043 less than 0.05, which means the provision of Solution Focused Brief Counseling for effective solutions to increase the learning motivation of class VIII students in Ash-Syafi’iyyah Islamic Middle School, Pakisaji Malang